Understanding the Force Deflection Behavior of NiTi Archwire at Distinct Bending Configuration: A Narrative Review in Vitro Studies - Munir, A.; Zulfiqar, S.; Joy Mathavan, J.; Sohail, A. (Engineering Journal, 2024)
This study aims to assess the optimal unloading force range for human comfort by considering NiTi archwires in different bending settings, based on previous research findings. All the relative data has been collected from different databases such as PubMed, Google Scholar, Scopus, Web of Science, and USM library. The publications from 2007 till February 2023 have been incorporated. Several parameters related to orthodontics, especially the usage of three brackets and three-point bending with respect to optimal tooth force were taken into consideration. These parameters, however, included various aspects like the shape memory effect, bending temperature, friction, and gingival/labial direction. ISO standards pertaining to the bending tests were also contemplated in this review. The study examined 74 articles related to orthodontic tooth movement, three brackets, and three-point bending. In fact, this review was done to analyze the force deflection behavior and related parameters to orthodontics. For this, among 74 selected research items, 15 studies gave information about the optimal tooth force, 8 focused on the optimal ranges, while 7 reports indicated the higher rates of tooth force. All these studies illustrated the considerable variation in methodology and clinical diversity in terms of applied forces. This article summarizes previous investigations on orthodontic tooth force, highlighting the ideal range of 0.2 to 1.5 N. It concludes that maximum force decreases with greater inter-bracket distance but increases with wire deflection and testing temperature. Proper force management is emphasized as crucial for preventing unwanted tooth movement and its biological consequences.
Keywords: NiTi archwire; orthodontics; force deflection; bending configuration